KEBIJAKAN PENDIDIKAN BAHASA ARAB PADA ANAK USIA DINI DI RAUDHATUL ATHFAL (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2015)
Arabic is one of the learning material that children learnwho studied at Raudlatul Athfal in Indonesia. This showsIndonesians have great attention to Arabiceven though the government does not have a policy related to it. Studythis focuses on the study of Arabic learning policies in twoRaudlatul Athfal in RA DWP UIN Sunan Kalijaga and RA RiyadusSalihin Tumut Sumbersari Moyudan Sleman. This research isqualitative field research. This is also a policy research.Data was collected by observation, interview and documentation techniques.The results of the study were first, the Indonesian government did not yet havepolicy on learning Arabic in Raudlatul Athfal. Second,Raudlatul Athfal DWP UIN Sunan Kalijaga and RA Riadlus SalihinTumut carried out Arabic learning with the modeldifferent. Arabic in RA DWP UIN Sunan Kalijaga was carried outonce a week with repetition of material every day, andthe material is Arabic vocabulary and its meaning. While RA RiyadusSalihin Arabic takes place with songs and games.